1996
DOI: 10.1093/oxfordjournals.aje.a008765
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in Drinking Water and Death from Acute Myocardial Infarction

Abstract: The relation between death from acute myocardial infarction and the level of magnesium in drinking water was examined using mortality registers and a case-control design. The study area comprised 17 municipalities in the southern part of Sweden that have different magnesium levels in the drinking water. Cases were men in the area who had died of acute myocardial infarction between ages 50 and 69 years during the period 1982-1989 (n = 854). The controls were men of the same age in the same area who had died fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(73 citation statements)
references
References 23 publications
3
67
3
Order By: Relevance
“…Contrastingly, five of the seven studies showed a statistically significant protective effect of drinking water magnesium against mortality from AMI ( Rubenowitz et al 1996Rubenowitz et al , 1999Rubenowitz et al , 2000, hypertensive disease ) and stroke (Yang 1998) for males and females.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Contrastingly, five of the seven studies showed a statistically significant protective effect of drinking water magnesium against mortality from AMI ( Rubenowitz et al 1996Rubenowitz et al , 1999Rubenowitz et al , 2000, hypertensive disease ) and stroke (Yang 1998) for males and females.…”
Section: Resultsmentioning
confidence: 77%
“…The remaining seven case control studies assessed concentrations of specific drinking water constituents, namely magnesium and calcium, and cardiovascular disease mortality. Of these, five studies reported no evidence of a statistically significant association between calcium concentrations and cardiovascular mortality with no consistent direction of association (Rubenowitz et al 1996(Rubenowitz et al , 2000Yang 1998;Rosenlund et al 2005). Two studies reported a protective effect of drinking water calcium on mortality from AMI for females (Rubenowitz et al 1999) and males and females combined (Yang et al 2006).…”
Section: Resultsmentioning
confidence: 97%
“…10 There are no available data for assessing the percentage that drinking water contributes to the total magnesium intake in the present study. Nonetheless, in the modern world intake of dietary magnesium is often lower than the recommended dietary amounts of 6 mg/kg per day.…”
Section: Discussionmentioning
confidence: 78%
“…The effects of magnesium deficiency on the heart are also complicated by intracellular potassium depletion and hypokalemia. (Woods and Fletcher, 1994;Jeremias et al, 2000;Rubenowitz et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The most important protective effect of magnesium during myocardial infarction is the restriction of the cellular loss of magnesium-adenosine tri phosphate, the essential substrate for many cellular reactions (Seelig, 1989;Rubenowitz et al, 1996;Swain and Kaplan-Machlis, 1999). Studies have also reported that magnesium also limits the loss of cellular potassium and this correlation needs further study with a large sample size.…”
Section: Resultsmentioning
confidence: 99%